2010
DOI: 10.3844/ajavsp.2010.65.70
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Broiler Chickens to a Weak Electromagnetic Field Reduces the Impact of a Simulated, Commercial Eimeria Infection

Abstract: Problem statement: In a previous study, the exposure of broiler chickens to a weak Electromagnetic Field (EMF) reduced the severity of a coccidiosis infection. The birds were infected by gavage into the crop which was not representative for the field situation. Approach: The possible anticoccidial activity of EMF was investigated in broiler chickens with a simulated, commercial coccidiosis infection. There was an uninfected and infected group not receiving further treatment. Another uninfected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, these results are supported by those obtained by Anne et al (2016) reported that a magnetic field can be used to inhibit E. coli, in their experiments, they used MW of 2 mT, 6 mT, and 10 mT for 6 hours and concluded that the maximum disinfection efficiency was 82.2% for bacteria exposed to a magnetic flux of 10 mT for 6 hours. Elmusharaf et al (2010) showed that weak electromagnetic field (5 µTesla) treatment for 30 min per day, protected against coccidiosis in broiler chickens.…”
Section: Effect Of Magnetized Water On Immunological Bacteriogical Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these results are supported by those obtained by Anne et al (2016) reported that a magnetic field can be used to inhibit E. coli, in their experiments, they used MW of 2 mT, 6 mT, and 10 mT for 6 hours and concluded that the maximum disinfection efficiency was 82.2% for bacteria exposed to a magnetic flux of 10 mT for 6 hours. Elmusharaf et al (2010) showed that weak electromagnetic field (5 µTesla) treatment for 30 min per day, protected against coccidiosis in broiler chickens.…”
Section: Effect Of Magnetized Water On Immunological Bacteriogical Pa...mentioning
confidence: 99%
“…Consequently, magnetic field was considered as a possible alternative to anticoccidial drugs in poultry production (Elmusharaf et al, 2010). Electromagnetic field exposure may have an anti-inflammatory effect (Vallbona and Richard, 1999;Montesinos et al, 2000) and beneficial effects on the nervous system have been recognized (Kaszuba-Zwoińska et al, 2005).…”
Section: Effect Of Magnetized Water On Immunological Bacteriogical Pa...mentioning
confidence: 99%
See 1 more Smart Citation